An Analysis of Legal Doctrines and Regulations for Genetic Privacy - Samuel F. Crowell (Studies in Law and Justice, 2023)
This paper explores the current state of genetic privacy, including the legal regimes of different countries, technological advances, and the scope of genetic privacy protection. The article also examines the judicial protection of genetic privacy, including legal means for data leakage and misuse. The study concludes that there are currently few legal doctrines or regulations that provide adequate protection for individuals and that it may be time to shift attention towards considering how and under what conditions to use genetic data while addressing the trade-offs between individual and societal interests.